2016
DOI: 10.1007/s10518-016-9943-2
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance evaluation of traditional timber Hımış frames: capacity spectrum method based assessment

Abstract: Timber constructions have been widely suggested to be seismically resistant based on post-disaster reconnaissance studies. This observation has, however, remained to a large extent anecdotal due to the lack of experimental work supporting it, especially for certain timber architectural forms, including traditional timber frame ''hımış'' structures. To fill this gap, the authors carried out an extensive full-scale testing scheme using frames of various geometrical configurations, tested under reverse-cyclic lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The frames were first tested in their bare state, and then repaired and re-tested with infill (brick and adobe; Figure 4b&c, respectively) and cladding (bağdadi and şamdolma, the latter being a central Anatolian variety of the former, with up to 5 times wider laths, see Figure 4d&e, respectively). The findings from the testing scheme were reported in detail elsewhere (see [49][50][51][52]). In the following, certain structural features of hımış houses are further discussed in the light of the findings of the aforementioned testing scheme and other resources.…”
Section: Constructive Features Of Himiş Structures and Their Effect Omentioning
confidence: 99%
“…The frames were first tested in their bare state, and then repaired and re-tested with infill (brick and adobe; Figure 4b&c, respectively) and cladding (bağdadi and şamdolma, the latter being a central Anatolian variety of the former, with up to 5 times wider laths, see Figure 4d&e, respectively). The findings from the testing scheme were reported in detail elsewhere (see [49][50][51][52]). In the following, certain structural features of hımış houses are further discussed in the light of the findings of the aforementioned testing scheme and other resources.…”
Section: Constructive Features Of Himiş Structures and Their Effect Omentioning
confidence: 99%
“…Similarly, Stellacci et al [2016] presented the case study of seismic performance of Gaiola and Borbone vernacular construction system and concluded that both construction systems consist significant earthquake-resistant features. Many vernacular building types such as Pombalino [Stellacci et al, 2017], Casa baraccata [Dipasquale et al, 2014], Himis (Aktas and Turer, 2016], Dhajji dewari [Ahmad et al, 2012], Ghumaune dhi [Gautam et al, 2016a], among others have been studied in the past. Seismic performance of urban vernacular building stocks is crucial to identify as their performance may alter the damage and death statistics, especially in traditional settlements.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional timber framed buildings are composite structures, characterized by upper storeys composed of a timber frame load-bearing system constructed on top of a masonry ground storey [25]. There are some post-disaster studies presenting a favourable seismic performance of the buildings [26][27][28][29].…”
Section: The Design Process For Reconstructionmentioning
confidence: 99%